Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Akuntansi Di Surabaya Untuk Memilih Karir Menjadi Akuntan Publik - Dewi Murdiawati (ITB AAS INDONESIA, 2020)
This research would like to examine the factors that can influence the selection of careers in the future of accounting students, especially to choose the profession as a public accountant. This research uses a quantitative approach with a questionnaire method and the number of samples used are 200 respondents. The test equipment uses multiple linear regression analysis using SPSS version 21. Partial results indicate that financial rewards, labor market considerations, professional training, professional recognition, social values, and work environments influence the interest of students in their future career choices, while professional risk is not proven to partially affect the interest of accounting students in choosing career. The results of the study simultaneously show that financial rewards, labor market considerations, professional training, professional recognition, social values, work environments, and professional risk jointly affect student interest in selecting careers in the future.